Bonding states of hydrogen for supported Ti clusters on pristine and defective graphene. (1st May 2023) - Ma, Li-Juan; Han, Ting; Hao, Zhichao; Wang, Jianfeng; Jia, Jianfeng; Wu, Hai-Shun
Abstract: To determine whether graphene-supported Ti clusters can synergistically store hydrogen through Kubas and spillover effect, we systematically investigate the growth pattern of Ti n (n = 1–10) clusters on pristine and defective graphene and analyze multiple types of bonding states of hydrogen in detail. For pristine graphene, the most stable Ti n (n = 1–10) clusters are the quasi-planar structure except for supported Ti4 and Ti5 . The Ti dissociation energies and the binding energy of Ti n clusters gradually increase with increasing n, which indicates that larger Tin clusters tend to form. Efficient spillover will occur on single-site Ti Catalysts at low hydrogen concentration due to the lower hydrogen spillover energy barrier (3.05 eV), while the energy barrier of hydrogen migration from Ti n (n = 2–7) clusters to graphene on the cluster is 5.34–6.82 eV. The Ti: H ratio is a maximum of 1:8 for the single-site Ti catalyst, while decreases with the Ti n cluster increases. Therefore, the pristine graphene-supported Ti nanoclusters are more suitable as substrates for hydrogen adsorbent rather than spillover. The introduced defects make Ti n clusters have three-dimensional conical configurations from n = 4. Ti3 and Ti6 are the most stable clusters. Moreover, the migration energy barriers of H atoms on them decrease from 6.54 eV to 6.82 eV–4.32 eV and 3.42 eV, respectively. Our results explain recent experimental phenomena [Appl Phys Lett 2015; 106: 083, 901. ACS Energy Lett 2022; 7 (7): 2297–2303] in depth at the molecular level. Graphical abstract: Image 1 Hydrogen can form three different main binding modes on graphene-supported Ti n (n = 2–7) clusters: atomic H, dissociated H2, and polarized H2 . Highlights: The Ti n /G clusters are quasi-planar except for n = 4, 5. Ti SAC has a lower hydrogen spillover energy barrier (3.05 eV). H migration barrier from Ti n (n = 2–7) to graphene is 5.34–6.82 eV. Defects reduce the size of Ti islands and increase the hydrogen storage density.